Tropical(ist) Fantasies: Bossa nova and samba in contemporary Lebanon - Messeder, Gabrielle (Revista Vórtex, 2018)
In this article, I provide an overview of the historical factors and contemporary issues that shape the presence of Brazilian music in Lebanon. I discuss the history of migration and remigration between the two countries, and how this transnational relationship has resulted in a small Brazilian population in Lebanon. I also discuss the music of Fairouz, the Rahbani brothers, and Ziad Rahbani; in particular, I examine Ziad's use of Brazilian music throughout his career. In the last section of this article, I present a case study of Xangô, a Beirut-based band who specialise in samba, bossa nova and MPB. Using ethnographic material, I outline the issues they face as professional performers, and how exoticism and stereotyping affects and shapes the production, performance and reception of Brazilian music in Lebanon.